Regularity Extraction from Non-Adjacent Sounds - Bendixen, Alexandra; Schröger, Erich; Ritter, Walter; Winkler, István (Frontiers in Psychology, 2012)
The regular behavior of sound sources helps us to make sense of the auditory environment. Regular patterns may, for instance, convey information on the identity of a sound source (such as the acoustic signature of a train moving on the rails). Yet typically, this signature overlaps in time with signals emitted from other sound sources. It is generally assumed that auditory regularity extraction cannot operate upon this mixture of signals because it only finds regularities between adjacent sounds. In this view, the auditory environment would be grouped into separate entities by means of readily available acoustic cues such as separation in frequency and location. Regularity extraction processes would then operate upon the resulting groups. Our new experimental evidence challenges this view. We presented two interleaved sound sequences which overlapped in frequency range and shared all acoustic parameters. The sequences only differed in their underlying regular patterns. We inserted deviants into one of the sequences to probe whether the regularity was extracted. In the first experiment, we found that these deviants elicited the mismatch negativity (MMN) component. Thus the auditory system was able to find the regularity between the non-adjacent sounds. Regularity extraction was not influenced by sequence cohesiveness as manipulated by the relative duration of tones and silent inter-tone-intervals. In the second experiment, we showed that a regularity connecting non-adjacent sounds was discovered only when the intervening sequence also contained a regular pattern, but not when the intervening sounds were randomly varying. This suggests that separate regular patterns are available to the auditory system as a cue for identifying signals coming from distinct sound sources. Thus auditory regularity extraction is not necessarily confined to a processing stage after initial sound grouping, but may precede grouping when other acoustic cues are unavailable.